Álgebras de incidência finitárias - Simone Francisco Ruiz (2013)
In this work we describe some basic properties of the finitary incidence algebra F I(P) of a partially ordered set P over a field. Among them, we describe the invertible elements, idempotents and regular elements of F I(P). We also investigate the relation between the isomorphisms, anti-automorphisms and involutions of F I(P) and the isomorphisms, antiautomorphisms and involutions of P. Besides these aspects, we examine the Zassenhaus properties of F I(P), of the incidence space I(P) and of the idealization F I(P)(+)I(P) of I(P)